CYD-Tetravalent Dengue Vaccine (CYD-TDV) to Children in Dengue Infectious Endemic Countries, Is It Necessary? : A Literature Review - Fabiola, Vanny Hilda; Trixie, Joue Abraham; Alexander, Michael (Universitas Ibn Khaldun Bogor, 2025)
Dengue is a tropical disease that is still a major health problem and effects almost half of the world’s human population, especially in Indonesia and affects adults and children. Many efforts have been made to control the disease and spread of Dengue vectors, one of that is the development of the dengue vaccine as part of prevention strategy. This study shows the profile, safety, efficacy, immunogenicity and effectiveness one of the dengue vaccines; Chimeric yellow fever 17 D virus – tetravalent dengue vaccine (CYD-TDV) which is currently in phase III trial and has been licensed in nearly 20 countries in the world. The research method in this literature review used several journals from 2015-2020 in media publications Google Scholar, NCBI, ResearchGate, WHO etc. CYD-TDV is a live attenuated vaccine which is development of dengue virus gene combine with a non-structural gene from the 17 D yellow fever vaccine strain. Vaccines are considered quite safe even though they still potentially causing systemic or local side effects. WHO Strategic Advisory Group of Express on Immunization (SAGE) recommends the use of CYD-TDV vaccine for individuals ≥9 years of age in dengue endemic areas with high transmission intensity, where seroprevalence is >70%. The use of vaccines in children aged 9 years has been shown to reduce the incidence of hospitalization due to Dengue fever. In Indonesia there’s not much information about the development, analysis, and data collection related to the use of dengue vaccine or CYD-TDV, so further research needs to be done.